Analysis of the Al-Qur'an Surah Thaha Verse 114 : Gaining Knowledge Through Prayer - Vina Syah Niar (Mazidah: Journal Of Educational Research, 2025)
Praying to Allah means asking something from the One Who Has Everything. If He is willing to answer that prayer, everything will be as easy as turning the palm of our hand. Because, Allah has the power to grant the prayer of someone who asks anytime and anywhere. Therefore, believe that prayer will definitely provide benefits. There will be no loss for those who want to pray. Islam, as explained in dozens of verses of the Koran, places science and scientists in a place of honor. This cannot be separated from the function and role of science. Knowledge is clearly the basic capital for someone to understand various things both related to worldly and spiritual matters. Prayers asking for additional knowledge need to always be said, asking Allah to increase that knowledge, because He is the source of all knowledge. When seeking knowledge, it is recommended to be patient and not rush so that we can learn optimally.